2018
DOI: 10.1016/j.jor.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Results of operative 4-in-1 patella realignment in children with recurrent patella instability

Abstract: The 4-in-1 patellar realignment is a good procedure in paediatric and adolescent patients with recurrent patella instability. Satisfactory results were observed with a minimal complication and redislocation rate in our series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Abouelsoud, 2015 1 Deie, 2003 8 Kumahashi, 2012 15 Lind, 2016 17 Matuszewski, 2018a 19 Matuszewski, 2018b 19 Nelitz, 2013 21 Nelitz, 2018 22 Pesenti, 2018 28 Uppstrom, 2019 40 Yercan, 2011 42 Benoit, 2007 2 Biglieni, 2011 3 Bonnard, 1990 4 Cootjans, 2013a 7 Cootjans, 2013b 7 Grannatt, 2012 11 Letts, 1999 16 Malagelada, 2018 18 Pesenti, 2017 27 Ronga The red bar indicates the 95% prediction interval. Prediction intervals illustrate which range of true effects expected to occur in similar studies in future settings.…”
Section: Random E Ects Modelmentioning
confidence: 99%
“…Abouelsoud, 2015 1 Deie, 2003 8 Kumahashi, 2012 15 Lind, 2016 17 Matuszewski, 2018a 19 Matuszewski, 2018b 19 Nelitz, 2013 21 Nelitz, 2018 22 Pesenti, 2018 28 Uppstrom, 2019 40 Yercan, 2011 42 Benoit, 2007 2 Biglieni, 2011 3 Bonnard, 1990 4 Cootjans, 2013a 7 Cootjans, 2013b 7 Grannatt, 2012 11 Letts, 1999 16 Malagelada, 2018 18 Pesenti, 2017 27 Ronga The red bar indicates the 95% prediction interval. Prediction intervals illustrate which range of true effects expected to occur in similar studies in future settings.…”
Section: Random E Ects Modelmentioning
confidence: 99%
“…Patients who experienced acute or recurrent patellar dislocations have different patterns of chondral injuries [54,101,102]. Several risk factors which predispose to patellofemoral instability have been described, such as patella alta, malalignment syndromes, ligamentous hyperlaxity, and dysplasia [103][104][105][106]. Recent studies demonstrated that most patients with patellofemoral instability have two or more coexistent pathoanatomical risk factors which synergistically predispose to the dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…In skeletally immature patients, standard TTOs such as the Trillat, Maquet, and Fulkerson are not suitable because of the risk to the proximal tibial physis and tibial tubercle apophysis. Options for physeal respecting distal realignment procedures include Galeazzi tenodesis, patella tendon shortening, modified Grammont procedure (medialization of the entire patella tendon and underlying periosteum, dissecting superficial to the open apophsysis), Roux-Goldthwait (translation and fixation of lateral half of the patella tendon, anteriorly, distally, and medially to the untouched medial half of the tibia), or combination procedures such as the "4 in 1" (lateral release, medial reefing, Insall tube realignment, and Roux-Goldthwait patella ligament transfer) and "3 in 1" procedure (Vastus medialis oblique (VMO) advancement, lateral release, and transfer of the medial third of the patellar tendon medially, sutured to the MCL and secured with anchors) ( Table 2) [34][35][36]. These aim to correct enlarged Q angles, similar to a TTO, but without threatening the physis or apophysis.…”
Section: Osseous Deformity Correction: Guided Growth or Osteotomymentioning
confidence: 99%
“…Therefore, recommended distal realignment procedures focus on soft tissue manipulations to minimize risk to the physis. These include the Roux-Goldthwait, modified Grammont, Galleazzi, and combination procedures [34][35][36]. Complications of these include incomplete correction, recurrent symptoms, patella tilt, increased PFJ contact pressures, anterior knee pain, and change in sport to non-weight bearing or lower level sport.…”
Section: Osseous Complicationsmentioning
confidence: 99%